Circular : 'The Spanish Workers' Defence of Democracy'
014_0026_001 NATIONAL COUNCIL OF LABOUR TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1 TRADES UNION CONGRESS Secretary: Sir Walter M. Citrine (Victoria 9820) THE LABOUR PARTY Secretary: J.S. Middleton (Victoria 8016) PARLIAMENTARY LABOUR PARTY Secretary: H. Scott Lindsay (Whitehall 6240) 18th August, 1936. To Trade Unions, Trades Councils, Constituency and Local Labour Parties. Dear Secretary, THE SPANISH WORKERS' DEFENCE OF DEMOCRACY. In order to secure the widest possible publicity for the Truth about the Spanish Workers' Defence of Democracy, the enclosed Leaflet has been issued by the National Council of Labour. It will be noted that the Leaflet also draws attention to the Special Appeal for contributions to the Fund for the relief of distress amongst the Spanish Workers. The leaflet is being sold at the subsidised price of 2s. 6d. per 1,000 copies, carriage paid, and it is hoped that this low price will enable every Organisation to order supplies. Please forward your requirements at the earliest possible moment on the attached Order Form. Yours sincerely, J.S. MIDDLETON, W.M. CITRINE, Joint Secretaries. THE SPANISH WORKERS' DEFENCE OF DEMOCRACY. Price: 2s. 6d. per 1,000, carriage paid. To The Labour Publications Dept., Transport House, Smith Square, London, S.W.1. Dear Sirs, Please send me ......................... copies of the Leaflet "Spanish Workers' Defence of Democracy", for which I enclose .....................in payment. Yours faithfully, NAME.................................................. ADDRESS............................................... ORGANISATION............................................. DATE...................... 292/946/14/26